Phallus aureus sp. nov. (Phallaceae, Basidiomycota) from Yunnan Province, China - Lv, Tong; Li, Yong-Rui; Ao, Cheng-Ce; He, Jun; Yu, Feng-Ming; Tang, Song-Ming; Li, Shu-Hong (Phytotaxa, 2022)
Phallus aureus is described as a new species from China and is characterized by an obovate, rugose, squamulose on the immature basidiomata surface, pseudostipe yellowish, grey volva, and pale yellow at the base becoming light yellow upwards. The new species is phylogenetically located in an independent lineage. A full description, colour photographs, illustrations, and a phylogenetic tree to show the position of new species are provided.